Seed Germination and Seedling Growth of Fenugreek (Methi) (Trigonella foenum graecum L.) Influenced by Water Extract of Eucalyptus Leaf Litter Vermicompost and Compost (Global Journal of Science Frontier Research, 2019)
Germination of seed is the fore most requirement of plant growth which influenced by several physical and chemical parameters. This factor either naturally found in the surrounding environment or some time added into the soil. Such supplementation is done either in the form of chemical or by an organic compound. Present study done to find out effect of different types of vermicompost and compost of Eucalyptus leaf litter on seed germination and seedling growth of Fenugreek seeds. The Result of present work indicated that there were > 97 % seeds were germinated treated by both vermicompost and compost. It has also found that dry, and green vermicompost of either 100 % or 50 % leaf litter significantly affect seedling growth more dominantly than compost treatment, and outcome also revealed that green vermicompost more significantly affect seedling growth than dry vermicompost . The average growth of the first, the second and the third day was 0.22 cm, 0.61 cm, and 1.29 cm respectively. Result also explore that second day growth was 5.3time higher than first day while 2.2 time higher in third day than second day. Population Standard Deviation, population Standard Variance and geometric mean were also determined at first (0.
Keywords: germinating seed; Fenugreek (Methi); vermicompost; compost; Eucalyptus leaf litter